Evaluation of an Afterschool Children’s Healthy Eating and Exercise Program - Dai, Chia-Liang; Nabors, Laura A.; King, Keith A.; Vidourek, Rebecca A.; Chen, Ching-Chen; Hoang, Nhung; Mastro, Katherine G. (International Journal of Child Health and Nutrition, 2014)
Background: The purpose of this study was to examine the feasibility of the Children’s Healthy Eating and Exercise Program (CHEE) in an afterschool program of an elementary school. Methods: Students in a low-income elementary school were recruited to participate in the program. Thirty-three children were in the intervention group. Twenty-four children in the comparison group were recruited from after school clubs in the same elementary school. The CHEE Program consisted of 18 sessions, featuring nutrition (20 min) and physical activity (40 min) lessons. Nutrition lessons were adapted from the Traffic Light Diet. Other lessons included MyPlate, my refrigerator, my lunchbox, and a healthy foods tasting activity. Multiple physical activities were utilized in the program including soccer, dance, relay races, tag, and other fun games. Data were collected at the beginning and end of the program. Results: Children in both groups reported eating more vegetables at the post-intervention measurement. Children in the intervention group indicated that they learned about healthy eating and new physical activities due to their participation in the program. Conclusions: Future studies are needed to discover barriers to behavior change as well as apply a more rigorous design to examine the impact of the CHEE Program.